Effect of light and protein phosphorylation on photoreceptor rod outer segment acyltransferase activity - Castagnet, Paula Ines (2002)
Rod outer segments (ROS) exhibit high acyltransferase (AT) activity, the preferred substrate of which being lysophosphatidylcholine. To study factors possibly regulating ROS AT activity purified ROS membranes were assayed under conditions under which protein kinase C (PKC), cAMP-dependent protein kinase (PKA), and phosphatases were stimulated or inhibited. PKC activation produced a significant increase in the acylation of phosphatidylethanolamine (PE) and phosphatidylinositol (PI) with oleate, it inhibited phosphatidylcholine (PC) acylation, and phosphatidylserine (PS) and phosphatidic acid (PA) acylation remained unchanged. ROS PKA activation resulted in increased oleate incorporation into PS and PI while the acylation of PC, PE, and PA remained unchanged. Inhibition of ROS PKC or PKA produced, as a general trait, inverse effects with respect to those observed under kinase-stimulatory conditions. ROS phosphatase 2A was inhibited by using okadaic acid, and the changes observed in AT activity are described. These findings suggest that changes in ROS protein phosphorylation produce specific changes in AT activity depending on the phospholipid substrate. The effect of light on AT activity in ROS membranes was also studied and it is reported that acylation in these membranes remains unchanged independent of the illumination condition used.